PENINGKATAN HASIL BELAJAR SISWA KELAS IV DENGAN MEDIA AUDIO VISUAL TERHADAP MATERI INFORMASI DARI TEKS DI SD NEGERI 066054 MEDAN: Penelitian Tindakan Kelas - Asri Maisun Putri; Syamsuyurnita; Silsia Risqha Revolina Siregar (STKIP Subang, 2024)
This research is a PTK, which aims to improve students' Indonesian language learning outcomes on Information from Text material through Audio Visual Media. Audio Visual Media is a learning media that contains sound (Audio) and Images (Visual) in the implementation of learning. This research was conducted in the odd semester of the 2024/2025 school year. This research was conducted over 2 cycles with 1 cycle of 2 meetings. The sample of this research is all fourth grade students of SD Negeri 066054 Medan Denai totalling 22 people. The data of this study were analysed with quantitative and qualitative approaches collected through observation and giving test questions. Based on the results of the study it can be concluded that, through the implementation of learning using Audio Visual media can improve student learning outcomes on the material of Information from Text. Learning outcomes increase every cycle seen from each meeting, namely meeting I average score of 55, meeting II of 58.5 meeting III of 73.5 and the last meeting or IV of 88.2. Audio Visual based learning media turned out to be very helpful for students in understanding and improving their learning outcomes related to the material that had been taught.